Strategies to improve hospital implementation of management functions that influence service behavior - Prayetno, Sugeng; Reimond Hasangapan Mikkael (Annals of Human Resource Management Research, 2025)
Purpose: This study analyzes how Leadership Style, Communication, and Control Systems influence Service Behavior and Hospital Performance in Majalaya Hospital’s Covid-19 response. Research Methodology: This study used SEM with AMOS 26, collecting data from 105 respondents via questionnaires and interviews to test four hypotheses on leadership, communication, control systems, service behavior, and hospital performance. Results: The study shows that Leadership, communication, and control systems positively impact service behavior, which in turn enhances hospital performance and business outcomes. Conclusions: This study emphasizes the role of leadership, communication, and control systems in shaping service behavior and improving hospital performance, service delivery, and efficiency. Limitations: This study is limited to Majalaya Hospital's Covid-19 response, restricting generalizability. Self-reported data may also have introduced a bias. Contribution: This study reinforces the role of leadership, communication, and control systems in service behavior. It advises hospitals to enhance their feedback, communication, and leadership for better performance.